Microbial and clinical disparities in pneumonia: insights from metagenomic next-generation sequencing in patients with community-acquired and severe pneumonia - Luo, Wang; Zhang, Shuhua; Sun, Jinhuan; Xu, Jianhui; Huang, Weihua; Hao, Ruiqing; Ou, Zhao; Wen, Ziyang; Wang, Daiwei; Xiao, Guanhua; Dong, Hangming (Frontiers in Microbiology, 2025)
BackgroundCommunity-acquired pneumonia (CAP) is a major global cause of death, with its varying symptoms and severity complicating diagnosis and treatment. Severe pneumonia (SP), a more critical form of CAP, has higher mortality and often requires intensive care. The identification of clinical markers to differentiate CAP from SP has the potential to improve treatment protocols and patient outcomes. Concurrently, metagenomic next-generation sequencing (mNGS) demonstrates significant promise in pathogen detection and in elucidating microbiome disparities between CAP and SP.MethodsThis retrospective study analyzed clinical and pathogen data from 204 patients diagnosed with CAP and 25 patients diagnosed with SP in the Department of Respiratory and Critical Care Medicine at the Zengcheng Branch of Nanfang Hospital, Southern Medical University, spanning the period from September 2022 to June 2023. Clinical characteristics were compared, and bronchoalveolar lavage fluid (BALF) samples underwent mNGS for microbial detection and characterization. Statistical analyses, encompassing Chi-square, Fisher’s exact test, Student’s t-test, and LEfSe analysis, were employed to compare clinical and microbiological data between the CAP and SP cohorts.ResultsPatients with SP were significantly older and exhibited higher incidences of sepsis, hypotension, tachycardia, multilobar infiltrates, and consciousness disorders compared to those with CAP. Elevated levels of C-reactive protein (CRP) and procalcitonin (PCT) were more frequently observed in SP patients. mNGS analysis identified diagnostic microbiology profiles between groups. Diverse microbiological profiles (> 5 species) were more common in SP patients (> 30% detection rate). Beta diversity analysis demonstrated significant differences in microbial community composition between CAP and SP groups (p = 0.001), though alpha diversity metrics showed no significant differences. Both LEfSe and ANCOM-BC2 analyses consistently identified Pseudomonas as a potential biomarker for SP and Streptococcus for CAP.ConclusionThe substantial differences observed in clinical characteristics, pathogen profiles, and microbiomes between patients with CAP and those with SP highlight the imperative need for comprehensive diagnostic methodologies in the management of pneumonia. mNGS has demonstrated substantial utility in informing personalized treatment strategies, with the potential to enhance clinical outcomes. Future research should prioritize elucidating the dynamics of microbial communities and their impact on pneumonia severity, with the objective of refining and optimizing therapeutic strategies.